Boosting the Students English Language Skill through Smartphones - Wahyuni, Retno Budi; Kuswardhani, Naniek (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Digitalization era could not be separated from using smartphones in people life activities. Everybody has got smartphones as they are handy to bring, not only easy to operate and to connect but also be connected. Therefore, most students use their smartphones during teaching learning process in the classroom during teaching learning process in the classroom, as they provide so many applications to be used. So, why dont we maximize their functions in the teaching learning process rather than keep asking students not to use their smartphones by updating status on their social media, browsing or playing games secretly. This paper is talking about how teachers use the social media to be interacted and be very useful during teaching learning process. The connectivity of internet provide by the campus is free, so the teachers could make a group of WhatsAp or Line used as media of giving and doing tasks. The paper talks about what application and activities used to be integrated and interesting process in teaching and learning English.